Analisis Ekonomi dan Dampak Pandemi COVID-19 terhadap Kunjungan Pasien Diabetes: Studi Kasus Poliklinik Pusat Diabetes RS Ngoerah, Bali, Indonesia - Saraswati, Made Ratna; Ayuningtyas, Dumilah (Jurnal Ekonomi Kesehatan Indonesia, 2025)
The COVID-19 pandemic has significantly impacted community activities, including social and economic aspects, as well as health behavior and healthcare services. Diabetes Mellitus (DM) is a chronic disease that requires continuous management to prevent chronic complications. Ngoerah Hospital (RS Ngoerah), Bali, Indonesia, is a type A hospital where DM patients generally present with complications. This study analyzes the impact of the COVID-19 pandemic on DM patient visits to the Diabetes Center Polyclinic at RS Ngoerah by considering economic aspects. This research is a retrospective study of patient visit data to the Diabetes Center Polyclinic at RS Ngoerah from 2019 to 2024, covering the time before, during, and after the COVID-19 pandemic. A descriptive analysis was carried out to observe changes in patient visits during each period. Furthermore, an aggregate analysis was conducted to examine the correlation between the number of patient visits and the number of detected COVID-19 cases, the COVID-19 pandemic timeline along with government regulations during the pandemic, and the economic condition reflected by the Gross Regional Domestic Product (GRDP) of Bali Province in the same year. The COVID-19 pandemic led to a decrease of up to 58.65% in DM patient visits to the Diabetes Center Polyclinic at Ngoerah Hospital. Directly, there was no significant correlation between the number of reported COVID-19 cases in Bali Province and the number of DM patient visits to the Diabetes Center Polyclinic at RS Ngoerah (r=0.262, p=0.155); however, other factors influencing the number of patient visits included government policies during the COVID-19 pandemic and the GRDP